2014
DOI: 10.1016/j.brainres.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sexually dimorphic genes in the neonatal mouse cortex and hippocampus

Abstract: The cerebral cortex and hippocampus are important for the control of cognitive functions and social behaviors, many of which are sexually dimorphic and tightly regulated by gonadal steroid hormones via activation of their respective nuclear receptors. As different levels of sex steroid hormones are present between the sexes during early development and their receptors act as transcription factors to regulate gene expression, we hypothesize that sexually dimorphic gene expression in the developing mouse cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 108 publications
8
59
0
Order By: Relevance
“…The current results confirm female-biased expression of Xist , Eif2s3x , Kdm6a , and Mid1 , consistent with our previous study [30]. In addition, they demonstrate that their expression is not dependent on prenatal TP levels, indicating that in the neonatal mouse cortex/ hippocampus, these four X-linked genes are mainly regulated by X-chromosomal gene dosage, rather than sex steroids (Figure 3).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current results confirm female-biased expression of Xist , Eif2s3x , Kdm6a , and Mid1 , consistent with our previous study [30]. In addition, they demonstrate that their expression is not dependent on prenatal TP levels, indicating that in the neonatal mouse cortex/ hippocampus, these four X-linked genes are mainly regulated by X-chromosomal gene dosage, rather than sex steroids (Figure 3).…”
Section: Discussionsupporting
confidence: 92%
“…Using gene expression microarrays with reverse transcription quantitative polymerase chain reaction, we have recently identified a group of sex-biased genes expressed in the neonatal mouse cortex/ hippocampus [30]. Based on the organizational effect of T on brain sexual differentiation, we hypothesized that some of these sexually dimorphic genes might be regulated by perinatal T, leading to the development of distinct neural functions and behaviors between the sexes.…”
Section: Introductionmentioning
confidence: 99%
“…The subtle magnitudes of the sex differences revealed in our study are very much in line with previous exploratory studies of sexually dimorphic gene expression [27, 33, 5860]. For example, in a microarray study by Yang et al [27] 613 of 4508 brain expressed genes differed by >onefold between the sexes, and 37 of those 613 genes displayed a fold difference of >1.2.…”
Section: Discussionsupporting
confidence: 90%
“…As an internal control, we indeed found that Kdm5d and Xist were the two most differentially expressed genes between XX and XY eNSCs at baseline. Given their known sexually dimorphic expression patters21 further supports the validity of our data set (Supplemental Table 1). For additional confidence, we selected 12 of our differentially expressed genes to validate by a secondary approach of qPCR, which showed similar expression differences that were identified within our RNA-seq dataset (Supplemental Fig.…”
Section: Resultssupporting
confidence: 76%
“…Unlike other studies that have focused on sex differences in the brain caused by genetic makeup6212829, our approach used a very specific cell type as opposed to gross brain tissue, as the latter may lack the sensitivity to observe nuances in gene expression, which may be masked by heterogeneous cell populations. This limitation has been observed when looking at DNA methylation in the brain, as it was found that global profiles are striking different between individual cells and that of heterogeneous cell populations within whole brain tissue30.…”
Section: Discussionmentioning
confidence: 99%